"I feel the mind enlarging itself": Anne Lister's gendered reading practices. Issue 4 (18th November 2022) - Matthews, Charley
Abstract: This article argues for the usefulness of deploying a trans lens to examine the diaries of Anne Lister (1791-1840). The author contends that a trans reading may expand possibilities for critical analysis of Lister's gender practices within the context of early-nineteenth-century white, upper-class Halifax society, in addition to existing labels such as "lesbian" and "queer." Examples to illustrate these possibilities are drawn from Lister's reading habits, facilitated by some initial quantitative analysis of Lister's own indexing practices. The article concludes that Lister structures their literary life to enable them to trans certain gender practices, and to fashion a livable gendered existence amidst the competing pressures of class, nationhood, financial security, self-determination, and sexual desire.